Pelatihan Spreadsheet Akuntansi sebagai Strategi Peningkatan Keterampilan Bekerja Siswa di Abad 21 - Arief Nurrahman; Aghni, Rizqi Ilyasa; Cahyani, Meita Dwi; Maulana, Muchamad Ziddan (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The Spreadsheet training program implemented by the accounting laboratory aims to improve job competition skills, as well as providing material and practical training related to the use of Spreadsheets. The target of this training activity is Pacitan Development Vocational School students. Participants who took part in the training were 21 students. Spreadsheet training is carried out offline in the accounting laboratory, FEB UNY. The training methods used are Focus Group Discussion and practice or simulation. This training went through two stages of implementation. First, a session providing material by the resource person as well as discussion resources with the students. Second, a Spreadsheet practice session directly using a computer guided by the speaker. Based on the evaluation results, the implementation of the Accounting Spreadsheet training went well and smoothly. The results of this training activity are that participants can understand material about accounting spreadsheets, master the concept of spreadsheet practice, and practice using spreadsheets in accounting transactions. Responses from participants regarding activities were also seen from the results of participant satisfaction surveys, suitability of material and practice, assessment of the quality of resource persons, and satisfaction with facilities which indicated that they were good or satisfied with attending the training.